Analisis Penerapan Etika Pengambilan Keputusan Publik dalam Kebijakan Penertiban Kawasan Kalijodo Tahun 2016 - Malchiel, David; Ramadhan, Doni; Agristya , Diva; Mochammad, Farrell (Jurnal Ilmu Administrasi Negara (JUAN), 2019)
DKI Jakarta as the center of government and national economy causing population growth rate in Jakarta to increase rapidly. Therefore, land is much needed to meet the needs of the people. Otherwise, there is need to create a Green Open Space of 30% as written in UU No 26 Tahun 2007 about Spatial Planning. In order to create comfortable, safe and sustainable urban spaces, Government of DKI Jakarta impose a policy for areas that should be green lines. One of the areas that has been successfully carried is Kalijodo area, North Jakarta. To decide which policy is used, the understanding of the ethical decision making is needed, the aspects are consecuentialist, deantological, and virtue ethics. The purpose of this research is to analyze the implementation of ethical decision making theory of curbing policy in Kalijodo area in 2016 by using quantitative descriptive approach with literature study method. This research indicates that the policy making process has been implemented the combination of three ethical approaches. The most influential approach is consecuentiatlist, followed by deantologist, and the last virtue ethics. Each of ethical decision making is imperfect, therefore ‘ethical triangle’ is needed so that there is a balance in decicion making process.